Role of the Sterol Regulatory Element Binding Protein Pathway in Tumorigenesis - Jiang, Tao; Zhang, Guangji; Lou, Zhaohuan (Frontiers in Oncology, 2020)
Metabolic changes are a major feature of tumors, including various metabolic forms, such as energy, lipid, and amino acid metabolism. Sterol regulatory element binding proteins (SREBPs) are important modules in regulating lipid metabolism and play an essential role in metabolic diseases. In the previous decades, the regulatory range of SREBPs has been markedly expanded. It was found that SREBPs also played a critical role in tumor development. SREBPs are involved in energy supply, lipid supply, immune environment and inflammatory environment shaping in tumor cells, and as a protective umbrella to support the malignant proliferation of tumor cells. Natural medicine and traditional Chinese medicine, as an important part of drug therapy, demonstrates the multifaceted effects of SREBPs regulation. This review summarizes the core processes in the involvement of SREBPs in tumors and provides a comprehensive understanding of the pathways through which natural drugs target the SREBP pathway and regulate tumor progression.